The open-door approach to locus standi by the African Commission on Human and Peoples' Rights in respect of its non-state complaints procedure: in need of reform? - Matusse, Angelo (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2006.